CHANGING BUSINESS TRENDS FOR ENVIRONMENT PROTECTION - Sharma, Jaya (International Journal of Research -GRANTHAALAYAH, 2015)
Businesses have been adopting every possible way to minimize their manufacturing cost in order to maximize their profit. Previously it was not a matter of concern for businesses to opt for some specified way of manufacturing, producing, marking and or packing so that the harmful impact on environment can be stopped. With the passing of time we are witnessing a world full of environmental problems like pollution, impure drinking water, poisonous crops and edibles. A huge amount of wastes is available everywhere to harm our earth in many ways may it be air, water of land. Thus there seems an urgent need to take some steps that may help to lessen such hazardous impacts on our environment. As business are an important part of our world it becomes a moral responsibility of all manufactures, industrialists and marketers to adopt the changing trends in their business which can help preventing our environment. The present paper tries to discuss some issues that are linked with finding out some new trends in business marketing and also suggests some views regarding better managements of waste material.